Respon Vibrasi Overall dan Temperatur Komponen Mesin Terhadap Misalignment Axial - Andi Kurniawan (KILAT, 2020)
Misalignment is one of the problems that often occurs in rotary equipment. In this paper, the observation was done to the rotary machine model in response to changes of axial misalignment by using vibration meter and infrared thermography camera. The model was a machine series, consisting of electric motor and disc which was connected by 3 Jaw flexible coupling. The shafts were positioned into several axial misalignment conditions to see the effect on the overall vibration value and its component temperature. The result of vibration observation showed that under certain conditions, by increasing shaft misalignment then the overall vibration value tends to decrease. With the decrease of overall vibration value, the machine condition was not in better condition. This was indicated by observing the temperature of the components in this condition, which showed the opposite fact. As misalignment increases, the temperature of the engine components also increases.